2021
DOI: 10.1021/acschembio.0c00865
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversification of Simple Synthetic Antibodies

Abstract: Antibodies possess properties that make them valuable as therapeutics, diagnostics, and basic research tools. However, antibody chemical reactivity and covalent antigen binding are constrained, or even prevented, by the narrow range of chemistries encoded in the canonical amino acids. In this work, we investigate strategies for leveraging an expanded range of chemical functionality to augment antibody binding properties. Using yeast displayed antibodies, we explored the presentation of noncanonical amino acids… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(87 citation statements)
references
References 127 publications
(287 reference statements)
4
83
0
Order By: Relevance
“…Recently, our lab demonstrated that we can secrete scFv-Fcs from yeast that contain noncanonical amino acids (ncAAs) at site-specific locations throughout the construct. [30] Some of these ncAAs contain functional groups that are amenable to "click" chemistry reactions [30,31] that we can leverage to add negatively charged functionalities at selected positions throughout the construct. The constructs in the present work contain additional negative charges only at the C-terminus, but as far as we are aware, no investigations have been made into whether the introduction of negative charge at different locations impact delivery efficiency.…”
Section: Chemmedchemmentioning
confidence: 99%
“…Recently, our lab demonstrated that we can secrete scFv-Fcs from yeast that contain noncanonical amino acids (ncAAs) at site-specific locations throughout the construct. [30] Some of these ncAAs contain functional groups that are amenable to "click" chemistry reactions [30,31] that we can leverage to add negatively charged functionalities at selected positions throughout the construct. The constructs in the present work contain additional negative charges only at the C-terminus, but as far as we are aware, no investigations have been made into whether the introduction of negative charge at different locations impact delivery efficiency.…”
Section: Chemmedchemmentioning
confidence: 99%
“…52 Guided by these sdAb-LC/A complex structures, we identified substitution positions in sdAbs that we deemed likely to result in photocrosslinking to LC/A based on 1) our recent developments in studying AzF-mediated photocrosslinking events on the yeast surface; 33 and 2) access to the AcFRS orthogonal translation system (OTS) to introduce this ncAA in response to the TAG codon in S. cerevisiae (Figure 1b, c). 33,53,54 . In addition, we chose several positions (JPU-A5 Q1; JPU-C10 Q1, Q44 and Y111; ciA-H7 Q1) that lie further away from the sdAb-LC/A interface with future investigations of conjugation-mediated augmentation of sdAb properties in mind, but still evaluated the properties of the resulting clones in this work.…”
Section: Single-domain Antibody Mutant Design and Orthogonal Translat...mentioning
confidence: 99%
“…The mutant plasmids were constructed by introducing TAG codons at the selected positions using typical Gibson assembly procedures (see also Materials and Methods). S. cerevisiae RJY100 57 was transformed with the corresponding pCTCON2 plasmid and pRS315_KanRMod_AcFRS, 33,53,54 which encodes for the AcFRS tRNA aminoacyl synthetase and the corresponding orthogonal tRNACUA for incorporation of ncAAs in response to the TAG codon.…”
Section: Display and Binding Validationmentioning
confidence: 99%
See 2 more Smart Citations